PROSPECTS OF STUDENT SELF-DEVELOPMENT IN A PANDEMIC: distance learning; innovative technologies; higher education seekers; pandemic - Parfinenko, Tetiana (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2022)
The article considers the use of innovative technologies in the distance learning system in a quarantine period. The purpose of the article is to theoretically substantiate the importance of student self-development in distance education and to define advanced learning technologies in this direction. The paper identifies personal characteristics of students belonging to generation Z and accordingly the theoretical bases of use of innovative technologies aimed at self-development of higher education seekers are substantiated. Given that the introduction of innovative technologies in the process of distance learning has to be structured and methodologically appropriate, the main elements of the development of distance learning courses have been considered. Research methods: theoretical (study, analysis, synthesis, generalization of scientific literature on the research issue, systematization and generalization of the obtained data), which enabled to clarify the advantages and disadvantages of distance learning in a pandemic; empirical (interviews, questionnaires, monitoring of the educational process), which contributed to the feasibility of introducing innovative technologies into the distance learning system in a pandemic and a study has been conducted on the Google Forms platform. A sample consisted of 50 first-year students of the School of International Economic Relations and Travel Business of V. N. Karazin Kharkiv National University. Results: problems of self-organization and reluctance for self-education and self-development of higher education seekers in a pandemic crisis have been identified; incomplete readiness of lecturers for educational activity in new conditions has been established. It is proposed to introduce innovative learning technologies into the educational process, which would be adapted for distance education and promote personal self-development. Conclusions. Forced isolation has shown a number of complications for both higher education and lecturers. However, research has shown that today’s youth are more flexible and progressive than the older generation and adapt more quickly to any change. Therefore, the use of innovative technologies in distance learning will increase students’ interest in educational material and the formation of their practical and research skills in the development of cognitive abilities and values, as well as motivate them for professional success